Scattering and Structures Essentials and Analogies in Quantum Physics - Povh, Bogdan; Rosina, Mitja; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
Quantum physics may appear complicated, especially if one forgets the "big picture" and gets lost in the details. However, it can become clearer and less tangled if one applies a few fundamental concepts so that simplified approaches can emerge and estimated orders of magnitude become clear. Povh and Rosina$1 (Bs "Scattering and Structures" presents the properties of quantum systems (elementary particles, nucleons, atoms, molecules, quantum gases, quantum liquids, stars, and early universe) with the help of elementary concepts and analogies between these seemingly different systems. The original German-language edition of this book was written for students preparing for their final oral examination in physics. By and large, the scope of the book in English has been essentially enlarged and thus will also be of interest for physicists in general.s
Photon Scattering -- Lepton Scattering -- Quasi-Elastic Lepton-Quark Scattering -- The Hydrogen Atom -- Many Electron Atoms -- Hadrons -- Covalent and Ionic Bonding -- Intermolecular Forces -- Cold Neutron Scattering -- The Nuclear Force and the Deuteron -- Quantum Gases -- Quantum Liquids -- Metals -- Nuclei $1 (BDroplets of a Fermi Liquid -- Stars, Planets, and Asteroids -- Elementary Particles -- The Early Universe.s
Keywords: Physics; Quantum physics; Observations, Astronomical; Astronomy -- Observations; Astrophysics; Nuclear physics; Elementary particles (Physics).; Quantum field theory; Quantum computers; Spintronics; Physics; Elementary Particles, Quantum Field Theory; Quantum Physics; Quantum Information Technology, Spintronics; Astronomy, Observations and Techniques; Astrophysics and Astroparticles; Particle and Nuclear Physics; Electronic books